Exploring Affect Organizational Citizenship Behavior Towards Happiness at Work of Islamic-Based Junior High School Teachers - Amalia, Hana Ayu; Kusmaryani, Rosita Endang; Saputra, Wildan Aji; Laabed, Elhadfa (Universitas Muhammadiyah Yogyakarta, 2025)
Teacher happiness in the workplace is an important factor in improving education quality, as it enables teachers to create conducive learning environments and enhances their psychological well-being and teaching effectiveness. This study explores how organizational citizenship behavior (OCB) affects teacher happiness at work (HAW) among Islamic-based junior high school teachers. Schools that support positive work environments can enhance teachers' OCB. This study uses a quantitative approach with a sample of 131 Islamic-based junior high school teachers. The instruments used to measure HAW and OCB were adapted from previous studies and analyzed using confirmatory factor analysis (CFA) and Partial Least Squares (PLS). The results show that the dimensions of OCB significantly affect HAW, with conscientiousness having the strongest effect. The path coefficients show that altruism (0.195), civic virtue (0.184), conscientiousness (0.282), courtesy (0.187), and sportsmanship (0.217) significantly affect HAW. The R-squared value of 0.828 indicates that OCB contributes 82.8% to HAW, meaning H6 is accepted. These findings offer key theoretical and practical implications for enhancing teacher happiness, particularly in Islamic-based school environments.